IMPACT OF POPULATION MIGRATION IN TESSO NILO NATIONAL PARK RIAU PROVINCE - Harapan Tua; Mimin Sundari (Sosiohumaniora, 2021)
The Tesso Nilo National Park is a conservation area that should be free from settlements and plantations. The migrants who come to the TNTN area are generally tough farmers who come from various ethnic groups such as Javanese, Batak, Palembang, even now there are Toro Bali. This study aims to look at Population Migration in Toro Jaya Hamlet, in the TNTN Area and the Impact of Population Migration on Forest Damage in the TNTN Area. This research uses a qualitative approach. Key Research Informants were selected by purposive and then using the snow ball sampling technique to determine the next informant. The method of data collection was done by means of in-depth interviews, focus group discussions, documentation. Then the data is analyzed based on the Interactive analysis model. The results show that population migration in TNTN has increased significantly coupled with the birth rate of the population, which on average are couples of productive age, which has made fertile land for population growth in TNTN. The smooth accessibility with the entry of public transportation vehicles (buses) to TNTN, especially Dusun Toro Jaya, coupled with the production of their “oil palm” plantation crops have also become a pull factor for many people to migrate to TNTN. This migration of the population has resulted in forest encroachment into residential areas and oil palm and rubber plantations. The encroachment will have an impact on the destruction and loss of native forest from Tesso Nilo National Park.